2014
DOI: 10.1097/won.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patient Education With Telephone Follow-up on Wound Healing in Adult Patients With Clean Wounds

Abstract: No differences in wound healing were found when patients who dressed their wounds at home using clean techniques versus patients who had their wounds dressed with sterile technique by professional nurses in a general outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…When ICCs are applied to homogenous populations (as in these cases), the ICC will be low as it is strongly influenced by the variance of the trait in the sample in which it is assessed . Chan and Lai used the BWAT to examine wound healing in clean open wounds excluding wounds with edema and induration and their sample of 126 wounds also showed minimal heterogeneity across necrotic tissue type and undermining. Jesada et al also found lower reliability estimates for the wound characteristic of necrotic tissue type (kappa range 0.37—0.60) in their study with certified wound care nurses assessing wounds at the bedside compared with experts assessing the same wounds based on photographs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When ICCs are applied to homogenous populations (as in these cases), the ICC will be low as it is strongly influenced by the variance of the trait in the sample in which it is assessed . Chan and Lai used the BWAT to examine wound healing in clean open wounds excluding wounds with edema and induration and their sample of 126 wounds also showed minimal heterogeneity across necrotic tissue type and undermining. Jesada et al also found lower reliability estimates for the wound characteristic of necrotic tissue type (kappa range 0.37—0.60) in their study with certified wound care nurses assessing wounds at the bedside compared with experts assessing the same wounds based on photographs.…”
Section: Discussionmentioning
confidence: 99%
“…Because its development, the BWAT has been used to assess wound healing in clinical research trials evaluating multiple wound treatments . These clinical studies have examined diverse wound treatments ranging from topical dressings and advanced wound therapies (negative pressure wound therapy, multiwave length light therapy and shock wave therapy) to patient education interventions . Takahashi et al used the total BWAT score to evaluate healing of stage 3 and 4 PrI treated with plastic wrap compared to moist gauze dressings and showed a significant difference in treatments with the BWAT total score as the outcome measure .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No tool was developed or validated specifically for calciphylaxis wounds and no prior study in calciphylaxis had evaluated wound healing with a dedicated wound assessment instrument. The Bates-Jensen Wound Assessment Tool (BWAT), which was selected to measure the primary study endpoint of calciphylaxis wound healing in the phase 2 study [25], is widely used for measuring and predicting wound healing in clinical settings and has been used successfully in randomized clinical studies for treatment of chronic wounds, including pressure ulcers, diabetic ulcers, and venous leg ulcers [26][27][28][29]. Thus, BWAT was selected as the primary efficacy measure in the phase 2 study to provide a well-accepted, objective, quantitative tool that could be applied systematically across study sites to assess changes in lesions over time.…”
Section: Bwat: a Chronic Wound Assessment Toolmentioning
confidence: 99%
“…Johnson-Mekota, et al [64] Outcome: Patients' and providers' satisfaction 58 Chan, et al [65] Outcome: Using scoring scale 59 Hill, et al 2009 [66] Outcome: Comparing accuracy of assessment 60 Salmhofer, et al [67] Outcome: Comparing accuracy of assessment • Page 4 of 9 •…”
Section: Study Selectionmentioning
confidence: 99%